Analisis Sentimen Masyarakat Terhadap Presiden dan Calon Presiden Terpilih 2024 Menggunakan NaÃ¯ve Bayes - Yusrizal, Muhammad; Sasongko, Theopilus Bayu (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
It has been more than 4 months since the KPU announced the results of the general election on Wednesday, 20 May 2024. With the election of pair number 2 as President and Vice President of the Republic of Indonesia for the 2024-2029 period, various public opinions, both positive and negative, emerged on Twitter. The main problem faced in this research is knowing the dominant sentiment of society towards Prabowo Subianto and Gibran Rakabuming after their election, whether negative or positive sentiment dominates. If you look at it with the naked eye, there are indeed many negative sentiments written by netizens through their tweets on Twitter. This research aims to analyze the sentiment of the Twitter community towards these two figures. Data collected through data crawling using tweet-harvest was 1520 tweets with several keywords such as Prabowo, Wowo, Minister of Defense, Gibran, and Samsul. The stages carried out on the data include preprocessing, translating, labeling, splitting the data, and applying the Naive Bayes algorithm. The analysis results show that positive sentiment is 39.02% and negative sentiment is 60.98%, with an accuracy value of 75%. With detailed values of 79% precision, 80% recall and 80% f1-score. It is hoped that this research will provide an overview of public opinion towards the elected President and Vice President as well as provide evaluation material for them and their supporting political parties to increase positive sentiment in the future.